Antibacterial and Optical Properties of Mn Doped ZnO Nanopowders Synthesized via Spray Drying and Subsequent Thermal Decomposition - Duman, Şeyma Duman; Mutlu, Büşra; Özkal, Burak (My University, 2020)
Mn doped ZnO nanopowders with homogenous particle distribution were synthesized using spray drying and thermal decomposition dual methods. Synthesis was carried out in spray drying slurry containing zinc acetate powders followed by calcining the as-prepared powders at 300, 400, and 500oC. Mn doping was achieved by adding manganese (II) acetate at different concentrations between 0.01-0.05 M during the synthesis. The obtained powders were characterized by a variety of characterization techniques. The results of phase analysis revealed that Mn-doped ZnO nanopowders having a single hexagonal structured ZnO phase. According to the results of microstructural and UV-vis characterizations; morphologies and optical properties of the Mn-doped ZnO nanopowders were affected by Mn doping. Furthermore, the results of this study exhibited that the addition of Mn have a significant influence on the antibacterial performance of the synthesized ZnO nanopowders.
Keywords: Nanobilim ve Nanoteknoloji; Kimya; Uygulamalı